Anammox granules show strong resistance to engineered silver nanoparticles during long-term exposure. (July 2018) - Zhang, Zheng-Zhe; Cheng, Ya-Fei; Xu, Lian-Zeng-Ji; Bai, Yu-Hui; Jin, Ren-Cun
Graphical abstract: Highlights: The long-term impact of AgNPs on anammox consortia was investigated firstly. 1–50 mg L −1 AgNPs had no adverse effects on the performance of anammox process. 1–50 mg L −1 AgNPs posed no threat to anammox bacteria ( Ca. Kuenenia ) in granules. Anammox consortia secreted more PN but less PS in response to the elevated AgNPs. Abstract: The increasing use of engineered Ag nanoparticles (NPs) in consumer products raises great concerns about their environmental impacts, but their potential impact on anaerobic ammonium oxidation (anammox) bacteria in wastewater treatment remains unclear. In this study, the response of anammox consortia inhabiting in granules to long-term exposure of AgNPs was investigated. The gradually increased stress of AgNPs (1, 10, 50 mg L −1 ) showed no adverse effects on the nitrogen removal performance and on the relative abundance of Ca. Kuenenia inhabiting in granules. Notably, in response to the escalating burden of AgNPs, anammox consortia tended to secrete more protein but less polysaccharide, and meanwhile increase the relative abundances of Ag + efflux protein SilA and regulatory protein SilR. Overall, these results suggested that the strong resistance of anammox granules to AgNPs might be mainly attributed to the defense role of extracellular polymeric substances and gene-based regulation of ion transport.